ANALISIS CITRA SATELIT LANDSAT 8 DAN DEMNAS UNTUK IDENTIFIKASI PROSPEK PANAS BUMI DI KABUPATEN ACEH TENGAH, PROVINSI ACEH: LANDSAT 8 AND DEMNAS IMAGES ANALYSES TO IDENTIFY GEOTHERMAL PROSPECT IN CENTRAL ACEH REGENCY, ACEH PROVINCE - Husin Setia Nugraha; Lano Adhitya Permana; Sukaesih (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
Combined analyses of Landsat satellite image and Digital Elevation Model Nasional (DEMNAS) are used to identify geothermal prospect areas. The analyses are applied in Aceh Tengah Regency because the information of springs exists in the regional geological map of Takengon. Two methods are applied to DEMNAS, namely the FFD method and circular features visual interpretation. Land Surface Temperature (LST) and Direct Principal Component Analysis (DPCA) methods are employed on Landsat 8 image. The appearance of circular features, anomalies of LST, and the existence of high-temperature mineral indicators are used to predict heat source indication. In addition, the FFD method is employed to indicate high permeability zones. The research shows that heat source indication is predicted at Mt. Telege Volcanic Complex within the District of Atu Lintang. The heat source is indicated by circular features appearance and LST anomalies within the area. Furthermore, the FFD method reveals an outflow zone near the hot spring of the northern part of Mt. Telege. In addition, the implementation of the DPCA method could not clearly separate between advanced argillic dan propylitic zones from their mineral indication values. It is due to mixing values among several mineral indicator values within the same pixel. In general, the application of the remote sensing method in Aceh Tengah Regency could help to indicate an early possibility of geothermal system exist within the area.